2011
DOI: 10.3892/ijmm.2011.749
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin, a potent suppressor of NF-κB and Smad activation in osteoblasts

Abstract: Abstract. Osteoclasts, the bone resorbing cells of the body, form when osteoclast precursors are exposed to the key osteoclastogenic cytokine receptor activator of NF-κB ligand (RANKL), a process requiring induction of NF-κB signaling. Quercetin is a ubiquitous plant-derived flavonoid with well documented antiinflammatory properties, in part, a consequence of its capacity to downmodulate the NF-κB signal transduction pathway. Consistent with this mechanism of action quercetin is reported to suppress osteoclast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…This study corroborates other previous studies on the anti-inflammatory and antiallergic properties of Allium cepa L. and quercetin [ 16 - 19 , 25 ], which might be linked to the ability of AcE an quercetin in down-modulate inflammatory processes through different signaling pathways such as NF-κB [ 43 - 45 ]. On the other hand, some authors discuss allergic reaction to onion.…”
Section: Discussionsupporting
confidence: 92%
“…This study corroborates other previous studies on the anti-inflammatory and antiallergic properties of Allium cepa L. and quercetin [ 16 - 19 , 25 ], which might be linked to the ability of AcE an quercetin in down-modulate inflammatory processes through different signaling pathways such as NF-κB [ 43 - 45 ]. On the other hand, some authors discuss allergic reaction to onion.…”
Section: Discussionsupporting
confidence: 92%
“…Of these products, flavonoids contained in fruits and vegetables have been found to be very active as anti-inflammatory agents [ 18 ]. The major flavonoid found in Allium cepa L. (onion) is quercetin (Qt) which exhibits many pharmacological properties such as anti-inflammatory and antioxidant effects [ 19 21 ]. Qt is also a potent inhibitor of in vitro osteoclastic differentiation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…TNFα further antagonizes BMP signaling by upregulating Smad ubiquitination regulatory factor 1 (Smurf1), promoting proteasomal degradation of bone morphogenetic signaling proteins [42]. Consistent with this data we have reported that multiple suppressors of NF-κB activation including the carotenoid beta-cryptoxanthin [43], the biphenol honokiol [19], vitamin K 2 [9], quercetin [20], zinc [24] and a pharmacological NF-κB inhibitor based on the NEMO binding domain [1] are all capable of rescuing the inhibitory effect of TNFα on BMP2 and/or TGFβ-induced Smad activation.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, we have recently reported that several natural compounds, long believed to possess anabolic and/or anti-catabolic properties, may protect bone by antagonizing NF-κB activation. Among these agents are vitamin K 2 [9], 17beta-estradiol [17], the carotene, p-hydroxycinnamic acid, the xanthophyll, beta-cryptoxanthin [18], honokiol, a component of Asian herbal teas used extensively in traditional Japanese and Chinese medicine [19], and the plant-derived flavonoid quercetin [20]. …”
Section: Introductionmentioning
confidence: 99%